2021
DOI: 10.1080/09540121.2021.1883506
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, empathy, and willingness to counsel patients with HIV among Indonesian pharmacists: a national survey of stigma

Abstract: This study aimed to assess the level of HIV treatment knowledge, empathy, and HIV stigma of pharmacy students and pharmacists working with patients as well as potential factors associated with stigma. This survey included 250 hospital pharmacists within 33 provinces and 1013 final-year pharmacy students from Java, the most populated island in Indonesia. The data were collected via Qualtrics® and distributed by WhatsApp. The mean age of the participants was (Mean ± SD) 24.68 ± 5.30 years, and 80.0% were female.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…The included studies were published between 2011 and 2022 and were conducted in seven countries: eight in the United States 2,23-29 and one each from Korea, 30 China, 31 United Kingdom, 32 Indonesia, 33 Singapore, 34 and Iran. 35 Eleven of the included studies used cross-sectional designs, two studies used randomized control trial designs, 24,34 and one of the studies used one group pretest-posttest intervention design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies were published between 2011 and 2022 and were conducted in seven countries: eight in the United States 2,23-29 and one each from Korea, 30 China, 31 United Kingdom, 32 Indonesia, 33 Singapore, 34 and Iran. 35 Eleven of the included studies used cross-sectional designs, two studies used randomized control trial designs, 24,34 and one of the studies used one group pretest-posttest intervention design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…28 Twelve (86%) studies included pharmacy students as participants and two (14%) studies informed pharmacy students and other health professional students or pharmacists. 28,33 Pharmacy students as participants ranged from first year through to fourth year students. Three of the included studies reported first-year level of pharmacy students as participants.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a positive emotion (19,24,25), awe may increase empathy for others (26). Empathy, an other-oriented prosocial affect including compassion, sympathy, and tenderness (27), is an effective factor for performing kindness (28) and lessening stigma toward stigmatized groups (5,29,30). A recent study have showed that awe elicited by classical serotonergic psychedelic increases empathy (31), which means that experiencing awe benefits to the improvement of empathy.…”
Section: Introductionmentioning
confidence: 99%
“…AIDS-related Stigma is a widespread social phenomenon. Many studies have been done to reduce it (29), but little research has investigated how to reduce AIDS-related stigma from the perspective of emotions, especially self-transcendent emotions, such as awe. Therefore, the purpose of the study is to examine the impact of awe on AIDS-related stigma and the mechanism underlying the association.…”
Section: Introductionmentioning
confidence: 99%